Methodological and Sociological Analysis About The Fatwa Of Majelis Tarjih Muhammadiyah Concerning To The Muslim Marriage With An Ahl Al-Kitab - Chamim Tohari (Jurnal Ilmiah Al-Syir'ah, 2018)
Relation between the different of religion comunity in the multicultural nation as in Indonesia be a natural phenomenon that it cannot be avoided. As to one of the problem that had appeared in this case is about wedding problem betweena moslem with the difference religion womans. Majority of the Indonesia religious scholars as scholar in Majelis Tarjih Muhammadiyah had been prohibiting wedding like that with various reason. while a part little of the contemporary moslem scholars have been permiting the wedding. The points which will discussed in this research is how is opinion of Majelis Tarjih Muhammadiyah about the law of wedding with the woman from Ahl Al-Kitab and its ijtihad methodology. This research should analyze the argumentation of the Majelis Tarjih that make forbidding a muslem married with the difference religion womans. This research using library research approach dan content analysis. The results of this research are: (1) Majelis Tarjih of Muhammadiyah forbidding the wedding with sad al-dzari’ah as its argumentation; (2) Majelis Tarjih’s opinion has been irrelevant because two reason, the mistake of methodology and the change of the Indonesian contemporary society (based on an empiric data). Keywords: Ahlu Kitab; Majelis Tarjih; Different Religion Marriage